Pengaruh Likuidtas Terhadap Struktur Modal Dengan Rasio Akivitas Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Konstruksi Non Bangunan Periode 2018-2022 - Fitriyani Fitriyani; Akhmadi Akhmadi (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This study aims to obtain emprical evidance of the effort of liquidity, activity on the company’s capital structure. The population used is the non-building construction sub-sector for the 2018-2022 period. The Sampling technique used is porposive sampling with certain criteria. So that 10 companies were obtained according to the criteria. Data analysis technique used in research include multiple linier regression analysys and path analysis. The result of the research test show that liquidity and activity have a significant impact on the capital structure of non-building cconstruction sub-sector companies. In addition, activity variables as intervening variables are able to mediate the relationship between liquidity and capital structure.